Rancang Bangun Aplikasi Sistem Monitoring Kupon Makan Di Pondok Pesantren Ngalah Menggunakan KTS (Kartu Tanda Santri) Berbasis RFID - Arrosidi, Shoffi; Lutfi, Moch. (Jurnal Ilmiah Informatika Global, 2023)
Along with the growth of the contemporary era, where technological advances occasionally experience rapid development and have provided many conveniences for mankind in everyday life. It promotes and facilitates human control of each system and can facilitate human work, including security-related tasks. One of the boarding schools in Pasuruan Regency is the Ngalah Islamic Boarding School. Pondok Ngalah was built on August 30, 1985 AD, or to coincide with Friday Pahing, the 14th of Dzulhijjah in 1405 Hijriyah, by its founder KH. M. Sholeh Bahruddin Kalam. Meal coupons are one of the most important cultures in the world of Islamic boarding schools. The meal coupon is proof that the student can take rice at the dormitory canteen. The student coupons are distributed in each dormitory and each student gets 60 coupons that can be used to collect rice within one month. In terms of each dormitory, coupons are used in one day, up to 2 coupons, but there are students who do not pay attention to the rules, and what's even worse, there are students who photocopy coupons to increase the number of coupons. Follow up with the student. Therefore, a coupon security system is needed that can be monitored by the parties concerned, namely using a tool that is already based on the Internet of Things by making a coupon security tool using KTS (Santri Identity Card). This electronic tool is designed to find out the availability of student meal coupons using RFID which produces a scanned program that can be printed in pdf format. The expected result of this test is to be able to find out the availability of student meal coupons every day.